Die mykenische Akropolis. Grabungen 1975-1980: Stratigraphie und Bebauung - Alram-Stern, Eva (Verlag der Österreichischen Akademie der Wissenschaften, 2020)
The second volume on the Austrian excavations of the years 1975-1980 on the acropolis of Aigeira aims at a reconstruction of the post-palatial Mycenaean settlement, based on stratigraphy and findings. Spatial analyses were executed on the basis of distribution patterns of installations as well as small finds, pithoi and pottery in situ showing a settlement consisting of households based on family structures which are characterized by storage, production of goods and feasting. Furthermore, the social grade of the inhabitants is underlined by a cult room as well as a fortification evident for a late phase of the settlement.Buch: http://e-book.fwf.ac.at/o:1468Beilagenmappe: http://e-book.fwf.ac.at/o:1469